Muzakki’s Intention in Paying Zakat - Afrida Yeni; Hasan Mukhibad (AFEBI Islamic Finance and Economic Review, 2020)
The purpose of this study was to examine the factors that influence muzakki's intention to pay zakat using the theory of planned behavior approach. The sample used 94 muzakki which were selected by Incidental Sampling technique. Methods of data analysis using the Structural Equation Model (SEM). The results showed that the intention of muzaki in paying zakat was positively influenced by the factors of attitude and behavior control. The intention to pay zakat has a positive effect on the intention of the muzaki to pay zakat. The behavioral control factor has a positive and significant effect on the willingness to pay zakat, while subjective norms have no effect on the intention to pay zakat. The implication of this research is that LAZ can create a supportive environment for muzakki in order to increase the desire and intention of muzakki to pay zakat.